Fysiska strukturer i Umeälvens gamla älvfåra och dess inverkan på laxsmoltens utvandringsframgång - Tegenfeldt, Viktoria (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2014)
The survival of hatchery reared smolts is generally low after release. To get a better understanding of what variables affecting migration success, Atlantic salmon smolts were studied during their out-migration in the old river channel in the lower part of river Umeälven. The area consists of shifting habitat and complex structures which causes difficulties for smolt on their migration out to sea. The aim of this study was to try to determine the effects of feed restriction, fin conditions and different physical barriers in the river, on the migratory behavior of Atlantic salmon smolts in the river Umeälven. The river was divided into six different sections using acoustic receivers strategically deployed along the river. Two-year old hatchery-reared smolts (n=150), in three different weight classes, were tagged with acoustic transmitters. The fish were released in late May 2013 and monitored while migrating downstream. A majority of the smolts migrated to the sea within two days after release. The smolts showed different migration speeds for different sections of the river. In sections containing large substrate size, steep incline and large proportion of rapids the smolts showed a significantly slower migration speed. The migration speed was similar for all weight classes and only a poor condition on the pectoral fin had a significant negative effect on migration speed. Compared to previous studies in the river, the survival and migration speed was high. At the time of release, the water flow was twice as high as in previous studies, which probably explained the higher migratory success.